How Does Inclusion Impact Employees in Organisations? Literature Review - Dudek, Alicja (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
Purpose: The purpose of this systematic literature review is to review the current state of research on the impact of inclusion in organisations on employees. Methods and materials used: The presented analysis of the empirical literature on the impact of inclusion was undertaken utilising two databases: Scopus and the Web of Science. In addition, a manual search of prominent journals within the ‘Organisational Behaviour and Human Resource Management’ category was performed. A total of 166 articles resulted from the conducted literature search, with 11 studies meeting the inclusion criteria. Main findings: Inclusion is a concept inspiring empirical research aiming to identify the positive impact of inclusiveness on employees in organisations. Empirical research indicates that inclusiveness has a positive impact on employees by stimulating their creativity, reducing turnover, increasing organisational commitment and citizenship behaviour, and improving employee well‑being and self- ‑esteem. The area that has received the most attention is inclusive leadership, but inclusive practices and, more broadly, inclusive organisations are also explored. Principal conclusion: The research focuses on the positive impact of inclusion on an organisation’s employees: their attitude, behaviour and intentions. The review has revealed that the dominant stream of research is inclusive leadership. What is lacking, however, is empirical research on how inclusion affects other stakeholders, so future studies should explore that.